Literary literacy and mental health in contemporary China: evidence from the China family panel studies - Hang Shi (Frontiers in Psychology, 2026)
Background Mental health problems impose a substantial social and economic burden in China. Yet population-based mental-health research has paid limited attention to literary literacy as a cultural resource embedded in everyday life. This study examines literary literacy as a multidimensional construct associated with adult mental health. Methods We analysed 114,448 person-wave observations from six China Family Panel Studies waves (2010, 2014, 2016, 2018, 2020, and 2022). The reconstructed literary-literacy score combines two direct domains—reading participation and language-cognitive capacity—using equal weights after within-wave standardization. Respondent education, parental education and family cultural resources were removed from the score and entered as covariates. The analysis used generalized propensity-score inverse probability weighting, covariate adjustment, individual fixed effects, a generalized additive percentile profile, an observed-variable parallel-path structural equation model and product-term moderation models. Results In the weighted covariate-adjusted model, a one-standard-deviation increase in reconstructed literary literacy was associated with a 0.058-SD higher mental-health score (95% CI [0.046, 0.070]). The within-person estimate was smaller ( β = 0.009, 95% CI [−0.001, 0.019]). In component models, the language-cognitive estimate was positive ( β = 0.075, 95% CI [0.066, 0.084]), whereas the average reading-participation estimate was close to zero ( β = −0.003, 95% CI [−0.009, 0.004]). The parallel-path model identified indirect coefficients through language expression, future confidence, interpersonal trust and life satisfaction, all with 95% confidence intervals above zero. The literary-literacy gradient was larger among women, rural residents, lower-income and lower-education groups, and adults aged 60 or older. Conclusion Reconstructing literary literacy from direct reading and language-cognitive indicators produced a positive adjusted association with adult mental health. The results locate the strongest average contribution in language-cognitive capacity and show that the joint profile varies across social groups.